If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3c + -1 = c Reorder the terms: -1 + 3c = c Solving -1 + 3c = c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-1c' to each side of the equation. -1 + 3c + -1c = c + -1c Combine like terms: 3c + -1c = 2c -1 + 2c = c + -1c Combine like terms: c + -1c = 0 -1 + 2c = 0 Add '1' to each side of the equation. -1 + 1 + 2c = 0 + 1 Combine like terms: -1 + 1 = 0 0 + 2c = 0 + 1 2c = 0 + 1 Combine like terms: 0 + 1 = 1 2c = 1 Divide each side by '2'. c = 0.5 Simplifying c = 0.5
| 3x-5-x=2x-3 | | 3ysquared= | | 3(2x+1)-2(3-2)=13 | | 15x-45/2=5x | | 1/3x3/8 | | (7a)x(2b)=0 | | 15/105 | | 9z+4-5z-5= | | -6(r-7)=-54 | | 8+9a=7 | | 4x+3+2y=11 | | 7x-4.23=0.2+2.57 | | 7x-4.23=0.2 | | -8(n-2)-2=-21-3n | | 3x=2(7x-3) | | 80+5x=7x | | 4(5r-5)=-20-7r | | -5=7-2x | | (3x-1)(x+2)=-1 | | -x-3(-5x-8)=136 | | (12^5)/(9^2)*(4^4) | | 12^5/9^2*4^4 | | 0.3x-2(0.1x+0.4)= | | (3a-9)/(3a-6)*(a/a^2-9) | | {(3a-9)/(3a-6)}*(a/a^2-9) | | f(x)=-3.25(-4.2) | | 18=2v+4 | | 6+2(5x-1)=84 | | 18-12a= | | 108=-6(3+3x) | | 5h-3h+9h= | | 42n-12=0 |